The EU's Fiscal Targets and Their Economic Impact in Finland - Henri Keränen; Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2016)
In this paper, we quantify time-varying fiscal multipliers using Finnish economic data and address questions about the design of the fiscal adjustment currently needed to comply with the EU's fiscal targets. We find that the necessary adjustment is likely to be larger than what is proposed in the current fiscal plans. The consolidation measures slow the economic recovery, and their cumulative multiplier effect on economic activity is close to 1 in the period 2016-2019. Despite the large fiscal multipliers, we do not find significant benefits in delaying the fiscal consolidation in terms of the present value of the GDP, at least given the current economic forecasts. Our results suggest that the emphasis of the government's fiscal plans on net revenue measures (defined as gross revenues minus transfers) seems to be well-placed.
Keywords: 330